The cross-border merger and acquisition strategy of Chinese multinational companies - Bian, Meilan (2017)
With the development of Chinese economy, more Chinese multinational firms choose to merge and acquire oversea companies. And their cross-border Merger and Acquisitions(CBM&As) have become so frequent during the last ten years. Now it is easy to discover that some international famous companies have been acquired by Chinese multinational firms. Among all the CBM&As, the motivations are diversified, for example, some Chinese state-owned firms try to acquire key natural resources such as the mines, ores or natural gas. Some private-owned high technology firms try to acquire key technologies to remedy its disadvantages. Some firms acquire the foreign firms just to enter the local markets for the complicated regulations. This research aims to explain and analyse the motivations that lead to the frequent CBM&As on these Chinese multinational firms. Not all Chinese firms succeeded in these CBM&As, and many Chinese firms failed during the CBM&AS, and some firms even cannot recover to the scales before the CBM&As. Therefore, this research would explain the reasons and strategies on those successful firms, then this research would also clarify why some Chinese firms failed during the CBM&As. This research has used 3 case studies to review the research, and the 3 cases includes that Lenovo acquired the IBM’s PC business, BOE acquired the NYDIS TFT-LCD and TCL acquired Thompson’s TV and DVD business.